Caracterización fenotípica del ganado caprino criollo en el cantón Catamayo, provincia de Loja - Landacay Barrera, Clemencia del Cisne (2014)
This research was done with creole goats with 261 animals (87 males) and (174 females), in three towns such as Catamayo, Tambo y San Pedro de la vendetta, located in Catamayo Canton, Province of Loja. There were studied 10 qualitative and phaneroptic characteristics such as: horns, wattles and beard. Colors of nose, hooves and mantle: Profiles: frontonasal duct, ear position, type of udder, rump conformation. Also 24 quantitative traits or morphometric: (raised in: Cross (ACZ), back (ADO) and the birth of the tail (ANC);) Lengths: ears (LORJ), head (LCBZ), neck (LCLL), rump (LGR), udder (LUBR), testicle (LTEST), former cane (LCNA) and rear (LCNP), corporal (LC), total (LT); Widths: (AC), meetings (AE), (AGRA) earlier rump and rear rump (AGRP), width (ACNA) former cane and cane back (ACNP); Perimeters: chest (PTO), former cane (ACNA) and rear (ACNP). Diameter: Sternal back (DDE); and weight body (PV).Furthermore, 9 ethnological four indices were estimated: head circumference (ICE), pelvic (IPE), body (ICO) and proportion (IPRO); functional four: relative depth of the thorax (IPRP), transverse pelvic (IPET), pelvic longitudinal (IPEL), thoracic Dactyl (RTD); one of motor ability: relative thickness of the cane (IERC).The objectives of the study were: 1. - analyze the phenotypic characteristics (qualitative and quantitative. Of the goats from Catamayo Canton, province of Loja. Also, 2. - socialize the alternatives for the improvement of the goat handling of the study area. Microsoft Excel templates were used for the analysis of data and then enter data in SPSS 18; for qualitative characteristics with frequency absolute and relative, for quantitative characteristics average arithmetic, median, mode and variation. Percentages of meat are 21.2% to 44% for females, and male them from 21.1% to 42%. The rate of milk in females is from 10% to 11%, males are from 10% to 12%; values of characteristics and morphological indexes allow to say that females and males, according to proportion are middle sized animals and curves because predominate the lengths on the width. With reference to the weight they are species with a medium volume, males and females (-) small and lightweight species (o).